2021
DOI: 10.1155/2021/9938658
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells: An Excellent Candidate for the Treatment of Diabetes Mellitus

Abstract: Mesenchymal stem cells (MSCs) are adult stem cells (ASCs) known for repairing damaged cells, exerting anti-inflammatory responses and producing immunoregulatory effects that can be significantly induced into insulin-producing cells (IPCs), providing an inexhaustible supply of functional β cells for cell replacement therapy and disease modeling for diabetes. MSC therapy may be the most promising strategy for diabetes mellitus because of these significant merits. In this paper, we focused on MSC therapy for diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Although the number of studies using MSCs for the treatment of T2DM is small, their findings support the safety of MSCs, with no severe adverse events observed during the course of these studies. 270 It was confirmed that MSC therapy potentially reduced fasting blood glucose and HbA1 C levels and increased C-peptide levels. However, these effects were short-term, and multiple doses were required to maintain the MSC effects.…”
Section: Endocrine Disorders Infertility/reproductive Function Recove...mentioning
confidence: 88%
“…Although the number of studies using MSCs for the treatment of T2DM is small, their findings support the safety of MSCs, with no severe adverse events observed during the course of these studies. 270 It was confirmed that MSC therapy potentially reduced fasting blood glucose and HbA1 C levels and increased C-peptide levels. However, these effects were short-term, and multiple doses were required to maintain the MSC effects.…”
Section: Endocrine Disorders Infertility/reproductive Function Recove...mentioning
confidence: 88%
“…However, although MSCs migrate to the pancreas, the differentiation into IPCs is minimal, and it is not the explanation for the possible regenerative effects induced by cell therapy. On injured pancreatic islets, beneficial effects are consequent to the immunomodulatory, anti-inflammatory and anti-apoptotic actions of the molecules secreted by MSCs, which protect endogenous β-cells, stimulate their regeneration and proliferation and ameliorate insulin resistance, reversing hyperglycemia, the main determinant of DCM [ 102 ]. Regarding cardiac repair, MSCs have protective and regenerative effects in several types of cardiovascular diseases [ 103 ].…”
Section: Preclinical and Clinical Approaches To Msc In Diabetes-induced Cardiac Complicationsmentioning
confidence: 99%
“…Since 2014, WJ-MSCs has been tipped to become the new gold standard for MSC-based therapies [ 82 ]. There has been much consent towards Wharton’s jelly as an interesting source of cells for clinical application, and relevant for translation to the field of DM cell therapy [ 84 , 85 ]. The most recent significance of the WJ-MSC’s clinical effectiveness derived from clinical trials involving in severe inflammation-based diseases, such as severe acute respiratory distress syndrome (ARDS) [ 86 , 87 , 88 ] in the coronavirus disease 2019 (COVID-19) context [ 89 , 90 , 91 ].…”
Section: Perinatal Cellsmentioning
confidence: 99%